Clinical- and Cost Effectiveness of a Guided Internet-Based Intervention for Children (12–18 Years) of Parents With Mental Disorders (iCHIMPS): Study Protocol of a Multicentered Cluster-Randomized Controlled Trial - Dülsen, Patrick; Barck, Katja; Daubmann, Anne; Höller, Alexandra; Zeidler, Jan; Kilian, Reinhold; Wiegand-Grefe, Silke; Baumeister, Harald (Frontiers in Digital Health, 2022)
Introduction Children of parents with mental disorders have a high chance of developing a mental disorder themselves. However, this at-risk group is regularly overlooked and typically not seen by any mental health professionals. Internet- and mobile-based interventions (IMIs) can provide a means of promoting mental health for children of parents with mental disorders. Objective The introduced study will evaluate the clinical- and cost-effectiveness of the iCHIMPS IMI in promoting mental health for children of parents with mental disorders. Methods A two-armed multicentered cluster-randomized controlled trial (cRCT) comparing the clinical- and cost-effectiveness of the iCHIMPS IMI in the intervention group (IG) to a treatment-as-usual (TAU) control group will be conducted. Recruitment will be handled at currently 21 adult mental health clinics throughout Germany. Participating families will be randomly divided into the two groups until the final sample size of 306 participating adolescents (age 12–18) has been reached. The adolescents in the intervention group will receive access to the IMI and can take part in up to eight intervention modules. Assessment will be conducted during the recruitment (baseline), 1-month, 2-months, and 6-month post-inclusion. Primary outcome is the mental health of the participating adolescents at 6-months post-inclusion as measured by the Youth Self Report score. Secondary self-report outcomes are mental wellbeing, self-efficacy, coping strategies and negative effects as well as mental health of the adolescents as reported by their parent(s). Included moderators are sociodemographic characteristics, working alliance, social support and the mental health diagnoses of the parents. Statistical analyses will be conducted on the intention-to-treat principle as well as with additional per-protocol analyses. Additionally, the cost-effectiveness as well as qualitative data concerning the adherence, acceptance, and feasibility of the IMI will be analyzed. Discussion The iCHIMPS cRCT examines the clinical- as well as cost-effectiveness of the iCHIMPS mental health promotion IMI for children of parents with mental disorders. This provides the opportunity to gain insights into an innovative as well as time- and location-independent form of support for this often-overlooked at-risk group. Additionally, the larger CHIMPS-NET project allows comparisons between internet-based and face-to-face interventions for a similar target group. Clinical Trial Registration www.ClinicalTrials.gov, identifier: DRKS00025158.